Evaluación ambiental de las descargas de aguas residuales de la granja porcina San José de la parroquia Casacay, cantón Pasaje - Carranza Rengel, Karen Lisbeth (2016)
The project identifies the problems of altering ecosystems and non-compliance with the maximum permissible limits stipulated in the Unified Text of the Environmental Legislation of the pig farm. The information described within the project is obtained through technical visits, interviews with the owner of the farm on which we carry out our work, direct observation and physical, chemical and biological analysis of the waste water from the farm. In which we describe some basic concepts related to pork production. Our objective of the research is to design an integrative proposal on the Management of the Residual Waters of the pig farm San Jose, through the application of biological system. The operation of the system consists of creating a floating carpet of plants, in which oxygen is pumped directly from the air through its leaf to the root system thanks to the alveolar type physiology benefiting the community that is around the implanted area , Possibly improving health conditions.